2017
DOI: 10.1136/jech-2017-209811
|View full text |Cite
|
Sign up to set email alerts
|

Influence of social relationship domains and their combinations on incident dementia: a prospective cohort study

Abstract: BackgroundSocial relationships consist of mutually related but distinct dimensions. It remains unclear how these domains independently contribute to incident dementia. This large-scale, prospective cohort study examines associations between the social relationship domains as well as their combinations and incident dementia among community-dwelling older adults.MethodsWe analysed data from 13 984 community-dwelling adults aged 65+ without long-term care needs living in Aichi prefecture in Japan. Incident dement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 80 publications
(68 citation statements)
references
References 41 publications
1
63
1
Order By: Relevance
“…For instance, meta-analysis across 148 articles mentioned active engagement in social activities could reduce risk for mortality. In particular, previous observational studies in Japan also found that collective social participation activities such as volunteering, sports clubs and hobbies among older adults lowered the risk of developing depressive symptoms,11–13 the incidence of functional disabilities,14–16 cognitive decline or dementia,17 18 falls19 and immature death 20–23…”
Section: Introductionmentioning
confidence: 96%
“…For instance, meta-analysis across 148 articles mentioned active engagement in social activities could reduce risk for mortality. In particular, previous observational studies in Japan also found that collective social participation activities such as volunteering, sports clubs and hobbies among older adults lowered the risk of developing depressive symptoms,11–13 the incidence of functional disabilities,14–16 cognitive decline or dementia,17 18 falls19 and immature death 20–23…”
Section: Introductionmentioning
confidence: 96%
“…This computer‐based test does not require specialists; therefore, it is useful as a test that can be performed by other local governments. It was also designed as a group activity because social isolation is a risk factor for dementia . Indeed, the classroom structure led to the formation of a community, and the increased interpersonal communication may have contributed synergistically to the improvement in cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“… 25 Level II or higher on the dementia scale (manifesting at least some symptoms, behaviors, or communication difficulties that hinder daily activities; level II corresponds to a 16-point rating on the Mini-Mental State Examination 24 ) was defined as dementia in this study, as has been described elsewhere. 23 , 26 …”
Section: Methodsmentioning
confidence: 99%